2009
DOI: 10.4137/cmt.s2027
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of ACE Inhibitors in Diabetes

Abstract: Angiotensin-converting enzyme (ACE) inhibitors have been FDA-approved for treating refractory hypertension since 1981. Since then, clinical investigations support the benefits of ACE inhibition (ACE-I) in pathologies like congestive heart failure, myocardial infarction, diabetes mellitus, chronic renal insufficiency, and atherosclerotic cardiovascular disease. Both, clinical trials and animal models of type I and type II diabetes have shown that hyperactivity of the angiotensin II signaling pathway contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
2
0
1
Order By: Relevance
“…Several studies have reported the anti-hypertensive properties of flavonoids ( Loizzo et al, 2007 ; Guerrero et al, 2012 ; Shafaei et al, 2016 ), which is also reflected in the strong binding affinity and molecular interactions of the isolated compounds (biochanin and 5,7,4′-trimethoxykaempferol) on docking with the crystal structure of Human Angiotensin Converting Enzyme (PDB ID: 1O86) ( Supplementary Figures S2A,B ). This correlates with the increased pancreatic β-cell and serum insulin level as ACE inhibitors have been shown to be not just therapeutic against hypertension but also reduces the risk of type 2 diabetes and its complications ( Abuissa et al, 2005 ; Ramos-Nino and Blumen, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the anti-hypertensive properties of flavonoids ( Loizzo et al, 2007 ; Guerrero et al, 2012 ; Shafaei et al, 2016 ), which is also reflected in the strong binding affinity and molecular interactions of the isolated compounds (biochanin and 5,7,4′-trimethoxykaempferol) on docking with the crystal structure of Human Angiotensin Converting Enzyme (PDB ID: 1O86) ( Supplementary Figures S2A,B ). This correlates with the increased pancreatic β-cell and serum insulin level as ACE inhibitors have been shown to be not just therapeutic against hypertension but also reduces the risk of type 2 diabetes and its complications ( Abuissa et al, 2005 ; Ramos-Nino and Blumen, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among antihypertensive drugs, ACE inhibitors have been well-studied in the case of PsD progression, and are defined as extensively used medications for the treatment of hypertension (HTN), congestive HF, diabetes, and even the prevention of kidney diseases 65 . According to the data analysis using the French Pharmacovigilance Database (FPVD), though psoriasis is considered one of the serious adverse events in patients receiving ACE inhibitors 66 , the mechanism of ACE-inhibitors induced/aggravated PsD is not fully deciphered.…”
Section: Possible Causesmentioning
confidence: 99%
“…В то же время на 14 сутки после индукции стрептозотоцинового диабета не было отмечено изменения в уровнях экспрессии генов ренина, ангиотензиногена и АПФ в клубочке почек крыс [11]. Тем не менее, препараты, ингибирующие РАС, а именно ингибиторы АПФ и антагонисты рецепторов к ангиотензину II (AII) находят широкое применение в лечении осложнений СД [12]. Приведённые результаты свидетельствуют о слабой изученности состояния РАС в динамике диабета, в частности, экспериментального.…”
unclassified